Students' challenges in the Mandarin classroom:A blended learning experience / Teoh Joo Tong and Chong Geeng Ling - Teoh, Joo Tong; Chong, Geeng Ling (Universiti Teknologi MARA Cawangan Kedah, 2018)
The purpose of study was to investigate the challenges of implementing the blended learning approach in Mandarin classes in a public university. A quantitative approach was used to analyze the data collected through an open-ended questionnaire. A total of 112 respondents were selected from students who were enrolled Mandarin course. The results indicated that the internet connectivity were the biggest challenges faced by blended mode students in Mandarin classes followed by technical glitches and human factors. A number of suggestions were highlighted by the respondents to improve the blended learning system.